Not Just Faster Horses: Telerehabilitation as a Necessary Evolution in Physical Therapy - Miguel Farraj; Julien Lebleu; Bruno Bonnechère; Joachim Van Cant (Journal of Orthopaedic & Sports Physical Therapy, 2026)
This editorial draws an analogy between the transition from “faster horses” to automobiles, and the digital transition facing musculoskeletal physical therapy. Musculoskeletal rehabilitation has long emphasized face-to-face sessions; digital solutions such as telerehabilitation have often been perceived as alternatives to conventional care. However, increasing rehabilitation demands, persistent gaps between sessions, and the need for long-term patient support highlight the importance of rethinking how physical therapists deliver care. We argue that telerehabilitation should not replace physical therapists, but rather extend their role through facilitating continuous monitoring, communication, education, and patient engagement. Successful implementation requires more than simply adopting new technologies—it requires clinicians to develop new skills, adapt professional habits, and integrate digital tools while preserving therapeutic relationships and patient-centered care. Just as innovation required moving beyond faster horses, the future of musculoskeletal physical therapy may depend on embracing new models of care rather than simply iterating on traditional approaches.